2005
DOI: 10.1093/humrep/deh870
|View full text |Cite
|
Sign up to set email alerts
|

Definition and prevalence of subfertility and infertility

Abstract: A common definition of sub- and infertility is very important for the appropriate management of infertility. Subfertility generally describes any form of reduced fertility with prolonged time of unwanted non-conception. Infertility may be used synonymously with sterility with only sporadically occurring spontaneous pregnancies. The major factor affecting the individual spontaneous pregnancy prospect is the time of unwanted non-conception which determines the grading of subfertility. Most of the pregnancies occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
275
2
19

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 482 publications
(301 citation statements)
references
References 34 publications
5
275
2
19
Order By: Relevance
“…However, when we examined these mice over a long period of time, we observed that these mice had significantly smaller litter size (P ¼ 0.02; Figure 4a) and significantly longer timeto-pregnancy (P ¼ 0.013; Figure 4b) than their wild-type littermates, suggesting diminished reproductive capacity, also known as subfertility in the homozygotes. 36 For instance, in spite of normal chow, the GALT-deficient mice had a maximum of three litters throughout their life (Figure 4b). Levels of follicle-stimulating hormone were not different between age-matched mutant and wild-type females (data Figure 3 Effect of galactose on growth in mice with different genotypes.…”
Section: Reduced Fertility In the Galt Gene-trapped Female Micementioning
confidence: 99%
“…However, when we examined these mice over a long period of time, we observed that these mice had significantly smaller litter size (P ¼ 0.02; Figure 4a) and significantly longer timeto-pregnancy (P ¼ 0.013; Figure 4b) than their wild-type littermates, suggesting diminished reproductive capacity, also known as subfertility in the homozygotes. 36 For instance, in spite of normal chow, the GALT-deficient mice had a maximum of three litters throughout their life (Figure 4b). Levels of follicle-stimulating hormone were not different between age-matched mutant and wild-type females (data Figure 3 Effect of galactose on growth in mice with different genotypes.…”
Section: Reduced Fertility In the Galt Gene-trapped Female Micementioning
confidence: 99%
“…Infertility (clinical definition) is currently defined as 1 year of unwanted nonconception with unprotected intercourse in the fertile phase of the menstrual cycle [1]. Fertility treatment may be medical, surgical or involve assisted conception where by the egg and sperm are brought into close proximity to facilitate fertilization.…”
Section: Introductionmentioning
confidence: 99%
“…4 Clinical infertility is recognized as the inability to conceive after 1 year or more of unprotected intercourse during the fertile phase of the menstrual cycle. 5,6 The baseline incidence of sterility is estimated at 1% of the general population, and this percentage does not change with age during the window of reproductive potential. Fertility begins to decline when women reach their late 20s and when men reach their late 30s.…”
mentioning
confidence: 99%